Cement suitable for coal bed gas well cementation and preparation method thereof

By using G-grade cement, active mineral materials and composite reinforcement materials in coalbed methane cementing cement, the problems of low early strength, large water loss and poor anti-trap performance in low-temperature environments are solved, and the rapid hydration and high-strength development of cementing cementing cement is achieved, and the toughness and anti-trap performance of cementing cementing cement is improved.

CN119683914AActive Publication Date: 2025-03-25JIAHUA SPECIAL CEMENT

Patent Information

Application Number
CN202411858326.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing coalbed methane cement cement has problems such as slow early strength development, large water loss, poor toughness, and poor anti-trapped performance in low-temperature environments.

Method used

A low-density cement system including G-grade cement, active mineral materials, composite reinforcement materials, mitigating agents, water-reducing agents and dispersants is adopted. Through the synergistic action of active component A and active component B, the cement hydration reaction is promoted, the early strength formation is accelerated, and the toughness and anti-trap-resistant properties of cement are improved through composite reinforcement materials.

Benefits of technology

In low temperature environments, the strength of cement develops rapidly, with good anti-trap performance and toughness, which can effectively solve the problems of low strength, large water loss and poor anti-trap performance in the early stage, and at the same time improve the overall performance of cementing cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192497450000071
    Figure BDA0005192497450000071
  • Figure BDA0005192497450000101
    Figure BDA0005192497450000101
  • Figure BDA0005192497450000111
    Figure BDA0005192497450000111
Patent Text Reader

Abstract

The invention discloses cement suitable for well cementation of coal bed gas and a preparation method of the cement. The cement comprises the following components in percentage by weight: 55-75wt% of G-grade cement, 15-20wt% of an active mineral material, 3-5wt% of a composite reinforcing material, 5-15wt% of a lightening agent, 1-3wt% of a fluid loss agent and 1-2wt% of a dispersing agent. The cement for coal bed gas well cementation has the advantages of being excellent in construction performance, rapid in strength development, good in anti-channeling performance and toughness and the like in a low-temperature environment. A large amount of solid waste is selected as a raw material for preparation, the solid waste absorption amount is increased, land resource waste and environmental pollution caused by solid waste stockpiling are reduced, and the method has the advantages of being environmentally friendly, low in cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field development cementing, and in particular to cement suitable for coal bed gas cementing and a preparation method thereof. Background Art

[0002] my country is rich in coalbed methane resources. In recent years, with the gradual development of coalbed methane industrialization in China, coalbed methane has become an important part of my country's petroleum energy. The main characteristics of coalbed methane wells are shallow gas layer burial, low bottom temperature generally between 25℃ and 45℃, low coal seam permeability and low pore pressure. Therefore, low-density cement slurry system is generally used for cementing.

[0003] Patent CN110054440A discloses a low-temperature, early-strength, low-density cement slurry system for coalbed methane cementing. The cement slurry system includes the following raw material components and their weight contents: oil well cement: 430 parts; slag powder: 430 parts; fly ash: 140 parts; floating beads: 0-140 parts; fluid loss reducer: 28-32 parts; early strength agent: 10-12 parts; expansion agent: 4-6 parts; dispersant: 10-12 parts; retarder: 6-8 parts; water: 600-920 parts.

[0004] Patent CN104194752A discloses a low-temperature early strength agent for coalbed methane well cementing and cement slurry containing the same. The low-temperature early strength agent has the following components: 1.5-2.5 parts by weight of calcium formate, 0.20-0.80 parts by weight of calcium sulfate, 0.30-1.0 parts by weight of aluminum sulfate, 0.20-1.0 parts by weight of sodium silicate, 0.20-0.80 parts by weight of sodium sulfate, 0.10-0.60 parts by weight of sodium aluminate, and 0.30-0.80 parts by weight of carbon nanotubes.

[0005] At present, there are few studies on cement for coalbed methane cementing. The existing cement slurry system has obvious deficiencies. The slow hydration rate of cement in low-temperature environments leads to a long cementing waiting time, which increases the risk of annular channeling, slow strength development, low early strength, poor toughness and other problems. Therefore, in order to meet the needs of coalbed methane well cementing development, it is particularly important to develop a low-temperature fast-setting, low water loss, high early strength, anti-channeling, high toughness, low-density cement system for coalbed methane well cementing for coalbed methane development and utilization. Summary of the invention

[0006] In order to overcome the defects and shortcomings of the above-mentioned prior art, the present invention provides a cement suitable for coalbed methane cementing and a preparation method thereof, so as to solve the problems of slow early strength development, large water loss, poor toughness and poor anti-channeling performance of cement slurry in coalbed methane cementing in a low temperature environment.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In one aspect, the present invention provides a cement suitable for coalbed methane cementing, comprising the following raw materials in weight percentage:

[0009] G grade cement: 55-75wt%;

[0010] Active mineral materials: 15-20wt%

[0011] Composite reinforcement material: 3-5wt%

[0012] Lightening agent: 5~15wt%

[0013] Fluid loss reducer: 1-3wt%;

[0014] Dispersant: 1~2wt%.

[0015] Furthermore, the active mineral material is a mixture of fly ash, microsilicon, lithium mica mine waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0016] Furthermore, the SiO2 content in the fly ash is 40-50wt%, and the Al2O3 content is 35-45wt%; the SiO2 content in the microsilicon is 96wt%, and the particle size of the microsilicon is 0.05-0.30μm; the SiO2 content in the lithium mica mine waste is 50-60wt%, the Al2O3 content is 25-30wt%, and the CaSO4 content is 3-5wt%; the SiO2 content in the wollastonite powder is greater than 50wt%, the CaO content is greater than 40wt%, and the average particle size of the wollastonite powder is 50μm.

[0017] Furthermore, the composite reinforcement material is a mixture of early strength material, elastic toughness material and micro-expansion material in a mass ratio of (14-16):(2-3):(2-3).

[0018] Furthermore, the early strength material is prepared by mixing active component A, active component B and reinforcing component in a mass ratio of 1:3:1, and the preparation method is as follows:

[0019] S1, mixing the active component A and the reinforcing component to obtain powder A;

[0020] S2, placing active component B in a ball mill and ball milling it at a speed of 500 rpm for 6 hours to obtain powder B;

[0021] S3, pneumatically mixing powder A and powder B to obtain an early strength material;

[0022] The early strength material of the present invention can provide an alkaline environment for the initial hydration reaction of cement, which can promote the hydration reaction of cement on the one hand; on the other hand, it can stimulate the activity of active component B, promote the activation and decomposition of solid waste residue in active component B, and promote the formation of Si 4+ 、Al3+ and Ca 2+ Plasma release accelerates the formation of hydration products. In addition, the active component A in the present invention can act as calcium silicate hydrate and calcium aluminosilicate hydrate crystal seeds in the early stage of hydration, provide a good nucleus effect in the cement hydration process, induce the formation of calcium silicate hydrate and calcium aluminosilicate hydrate in the cement hydration process, promote cement hydration and thus improve the early strength of cement.

[0023] Preferably, the active component A is prepared by mixing carbide slag, biomass slag and aerated concrete waste in a mass ratio of 5:4:1, and the preparation method is as follows:

[0024] S11, placing carbide slag, biomass slag and aerated concrete waste in a ball mill according to a mass ratio of 5:4:1, with a liquid-to-solid ratio of 1.0, and ball milling at a speed of 400 rpm for 72 hours to obtain slurry A;

[0025] S12, placing slurry A in a sealed stirring tank, adding 1 wt% of the solid mass of the slurry A in a dispersing stabilizer, stirring at a temperature of 80° C. for 72 h, to obtain slurry B;

[0026] S13, placing slurry B in a centrifugal device for liquid-solid separation, and drying the solid phase at the bottom of the liquid-solid separation into dry powder to obtain active component A;

[0027] More preferably, the CaO content in the carbide slag is 65-70wt%, and the pH is 12-13; the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the particle size is less than 325 mesh; the aerated concrete waste is composed of tobermorite, semi-crystalline CSH (I), CSH gel and silicon dioxide, and the powder fineness is less than 600 mesh after crushing and grinding; the dispersion stabilizer is a mixture of ketone-aldehyde condensation product and microcrystalline cellulose;

[0028] The active component A of the present invention utilizes carbide slag, biomass slag and aerated concrete waste to react under wet grinding conditions to generate calcium silicate hydrate and calcium aluminosilicate hydrate. The aerated concrete waste contains a large amount of tobermorite, which can serve as a nucleation site for calcium silicate and calcium aluminosilicate hydrate, greatly accelerating the formation of calcium silicate hydrate and calcium aluminosilicate hydrate and promoting cement hydration reaction.

[0029] Preferably, the active component B is prepared by mixing modified zirconium silicon slag, silicon manganese slag, phosphorus slag and alkaline slag in a mass ratio of 3:2:1:1, and the modified zirconium silicon slag is prepared by making slurry C from zirconium silicon slag, and the slurry C is subjected to solid-liquid separation after neutralization, water washing and impurity removal, and then high-temperature drying and grinding to obtain the product;

[0030] More preferably, the modified zirconium silicon slag has a SiO2 content of ≥90wt%, a neutral pH, and a powder particle size of less than 325 mesh; the powder particle size of the silicon manganese slag is less than 325 mesh, the SiO2 content is 35-40wt%, the Al2O3 content is 9-12wt%, the CaO content is 25-28wt%, and the MgO content is 6-11wt%; the SiO2 content of the phosphorus slag is 35-40wt%, and the CaO content is 42-48wt%; the CaCO3 content of the alkali slag is 40-45wt%, the CaSO4 content is 7-10wt%, and the CaCl2 content is 10-14wt%;

[0031] The active component B of the present invention contains a large amount of amorphous SiO2 particles, which are highly active and can quickly react with cement hydration product Ca(OH)2 to accelerate cement hydration. At the same time, the active component B also contains a small amount of MgO and CaSO4, which can promote the crystallization of calcium aluminate through synergistic effect with the reinforcing component on the one hand, and can form Mg(OH)2 in the cement hydration process on the other hand, thereby enhancing the cementitiousness and sealing properties of cementing stone, and thus improving the anti-channeling ability of cementing stone.

[0032] Preferably, the reinforcing component is a mixture of lithium silicate and aluminum sulfate in a mass ratio of 1:2;

[0033] More preferably, the purity of the lithium silicate is greater than 98 wt %, and the purity of the aluminum sulfate is greater than 98 wt %.

[0034] The reinforcing component of the present invention can react with free hydroxide ions (OH - ) and calcium ions (Ca 2+ ) reaction to generate silicate gel and calcium silicate, which fill the micropores and gaps of the hydration product, thereby improving the density of the matrix. The generated silicate gel and calcium silicate further promote the formation of hydrated calcium silicate and hydrated calcium aluminosilicate through synergistic reinforcement with the active component A; the reinforcement component can also promote the crystallization of ettringite together with the various ions released by the active component B. 4+ 、Al 3+ and Ca 2+ The consumption of plasma further promotes the hydration of cement and the dissociation and activity release of active component B, thereby promoting the formation of early strength. + Accelerate the destruction of the early hydration product film covering the cement particles and speed up the hydration process.

[0035] Furthermore, the elastic and tough material is prepared by mixing ethylene-butyl acrylate copolymer and cellulose acetate butyrate in a mass ratio of 5:2, which are crushed into fine powder and then modified by low-temperature plasma.

[0036] Furthermore, the butyl acrylate content in the ethylene-butyl acrylate copolymer is 33-37 wt %; the acetyl content in the cellulose acetate butyrate is 12-15 wt %, and the butyryl content is 32-35 wt %.

[0037] Furthermore, the micro-expanding material is a mixture of hectorite and magnesite tailings in a mass ratio of 1:3; preferably, the content of lithium magnesium silicate in the hectorite is >99wt%; the content of MgO in the magnesite tailings is 38-42wt%, and the content of SiO2 is 15-18wt%.

[0038] Furthermore, the lightening agent is hollow glass microspheres with a density of 0.44 to 0.48 g / cm 3 , Dv50 is 40μm, and the compressive strength is >4000psi; the fluid loss reducer is 2-acrylamide-2-methylpropanesulfonic acid / acrylamide copolymer; and the dispersant is sulfonated acetone formaldehyde condensate.

[0039] On the other hand, the present invention also provides a method for preparing cement suitable for coalbed methane cementing. The preparation method is as follows: G-grade cement, active mineral material, composite reinforcing material, lightening agent, fluid loss reducer and dispersant are mixed evenly in various proportions to form dry powder, thereby obtaining cement suitable for coalbed methane cementing.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The coalbed methane cementing cement of the present invention has excellent construction performance under low temperature environment, rapid strength development, good anti-channeling performance and toughness, etc. In addition, the present invention selects a large amount of solid waste as raw materials for preparation, increases the solid waste disposal capacity, reduces the waste of land resources and environmental pollution caused by solid waste storage, and has the characteristics of green environmental protection and low cost.

[0042] 2. The composite reinforcement material of the present invention provides an alkaline environment for the initial hydration reaction of cement, which promotes the hydration reaction of cement and dissolves SO4 2- On the one hand, it jointly promotes the formation of hydration products such as ettringite; on the other hand, it provides hydrated calcium silicate and hydrated calcium aluminosilicate seeds for the initial stage of cement hydration, provides a good nucleus effect in the process of cement hydration, induces the formation of hydrated calcium silicate and hydrated calcium aluminosilicate in the process of cement hydration, further promotes cement hydration and thus improves the early strength of cement.

[0043] 3. The composite reinforced material of the present invention is obtained by blending ethylene-butyl acrylate copolymer and cellulose acetate butyrate into powder and mixing them in a Z-type kneader. Under strong shearing and thermal effects, the elastic-tough material formed after mixing has improved elasticity, toughness, strength, etc.; the surface is modified by low-temperature plasma, which improves the surface tension and hydrophilicity of the elastic-tough material, enhances the bonding between the elastic-tough material and the cement interface transition zone and the internal pore structure, and the surface of the elastic-tough material is covered with hydration products, so that the bonding with the cement matrix is ​​stronger.

[0044] 4. The composite reinforcement material of the present invention can not only improve the stability of cement paste and reduce the water loss of cement paste through the combined action of hectorite and magnesite tailings, but also lithium magnesium silicate can enhance the bonding between cement hydration products, improve the density of cement system, and thus improve its strength development. In addition, the Mg(OH)2 formed by hydration in alkaline environment provided by the early strength material of the present invention and the calcium aluminate generated under the promotion of the early strength material synergistically enhance the expansion of cementing stone, improve the bonding and sealing of cement stone, and thus improve the anti-channeling ability of cementing stone. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] In the embodiment of the present invention, the G-grade cement is provided by Jiahua Special Cement Co., Ltd.; the fluid loss additive is 2-acrylamide-2-methylpropanesulfonic acid / acrylamide copolymer; and the dispersant is sulfonated acetone formaldehyde condensate.

[0047] Example 1

[0048] As a preferred embodiment of the present invention, the specific composition of the cement suitable for coalbed methane cementing in this embodiment is shown in Table 1 below:

[0049] Table 1

[0050] raw material Weight ratio (wt%) G grade cement 55 Active mineral materials 20 Composite reinforcement materials 5 Lightening Agent 15 Fluid Loss Additive 3 Dispersants 2

[0051] In this embodiment, the active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0052] In this embodiment, the composite reinforcement material is a mixture of early strength material, elastic toughness material and micro-expansion material in a mass ratio of 14:3:3.

[0053] In this embodiment, the lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 ,Dv50 is 40μm, compressive strength>4000psi.

[0054] G-grade cement, active mineral material, composite reinforcement material, fiber material, lightening agent, fluid loss additive and dispersant were weighed according to the weight ratio in Table 1 and mixed evenly to obtain cement 1# for cementing.

[0055] The cement slurry was prepared by using cement 1# for cementing in this embodiment with reference to GB / T19139 standard, and the water-cement ratio was 0.6 to obtain cement slurry system 1# for cementing.

[0056] Example 2

[0057] As a preferred embodiment of the present invention, the specific composition of cement suitable for coalbed methane cementing in this embodiment is shown in Table 2 below:

[0058] Table 2

[0059] raw material Weight ratio (wt%) G grade cement 65 Active mineral materials 17.5 Composite reinforcement materials 4 Lightening Agent 10 Fluid Loss Additive 2 Dispersants 1.5

[0060] In this embodiment, the active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0061] In this embodiment, the composite reinforcement material is a mixture of early strength material, elastic toughness material and micro-expansion material in a mass ratio of 14:3:3.

[0062] In this embodiment, the lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 ,Dv50 is 40μm, compressive strength>4000psi.

[0063] G-grade cement, active mineral material, composite reinforcement material, fiber material, lightening agent, fluid loss additive and dispersant were weighed according to the weight ratio in Table 2 and mixed evenly to obtain cement 2# suitable for cementing.

[0064] The cement slurry was prepared by using cement 2# for cementing in this embodiment with reference to GB / T19139 standard, and the water-cement ratio was 0.6 to obtain cement slurry system 2# for cementing.

[0065] Example 3

[0066] As a preferred embodiment of the present invention, the specific composition of the cement suitable for coalbed methane cementing in this embodiment is shown in Table 3 below:

[0067] Table 3

[0068]

[0069]

[0070] In this embodiment, the active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0071] In this embodiment, the composite reinforcement material is a mixture of early strength material, elastic toughness material and micro-expansion material in a mass ratio of 14:3:3.

[0072] In this embodiment, the lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 ,Dv50 is 40μm, compressive strength>4000psi.

[0073] G-grade cement, active mineral material, composite reinforcement material, fiber material, lightening agent, fluid loss additive and dispersant were weighed according to the weight ratio in Table 3 and mixed evenly to obtain cement 3# for cementing.

[0074] The cement slurry was prepared by using cement 3# for cementing in this embodiment with reference to GB / T19139 standard, and the water-cement ratio was 0.6 to obtain cement slurry system 3# for cementing.

[0075] Example 4

[0076] As a preferred embodiment of the present invention, the specific composition of the cement suitable for coalbed methane cementing in this embodiment is shown in Table 4 below:

[0077] Table 4

[0078] raw material Weight ratio (wt%) G grade cement 75 Active mineral materials 15 Composite reinforcement materials 3 Lightening Agent 5 Fluid Loss Additive 1 Dispersants 1

[0079] In this embodiment, the active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0080] In this embodiment, the composite reinforcement material is a mixture of early strength material, elastic toughness material and micro-expansion material in a mass ratio of 16:3:3.

[0081] In this embodiment, the lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 ,Dv50 is 40μm, compressive strength>4000psi.

[0082] G-grade cement, active mineral material, composite reinforcement material, fiber material, lightening agent, fluid loss additive and dispersant were weighed according to the weight ratio in Table 4 and mixed evenly to obtain cement 4# for cementing.

[0083] The cement slurry was prepared by using cement 4# for cementing in this embodiment with reference to GB / T19139 standard, and the water-cement ratio was 0.6 to obtain cement slurry system 4# for cementing.

[0084] Example 5

[0085] As a preferred embodiment of the present invention, the specific composition of the cement suitable for coalbed methane cementing in this embodiment is shown in Table 5 below:

[0086] Table 5

[0087] raw material Weight ratio (wt%) G grade cement 75 Active mineral materials 15 Composite reinforcement materials 3 Lightening Agent 5 Fluid Loss Additive 1 Dispersants 1

[0088] In this embodiment, the active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste and wollastonite powder in a mass ratio of 3:2:1:1.

[0089] In this embodiment, the composite reinforcement material is a mixture of an early strength material, an elastic toughness material and a micro-expansion material in a mass ratio of 8:1:1.

[0090] In this embodiment, the lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 ,Dv50 is 40μm, compressive strength>4000psi.

[0091] G-grade cement, active mineral material, composite reinforcement material, fiber material, lightening agent, fluid loss additive and dispersant were weighed according to the weight ratio in Table 5 and mixed evenly to obtain cement 5# for cementing.

[0092] The cement slurry was prepared by using cement 5# for cementing in this embodiment with reference to GB / T19139 standard, and the water-cement ratio was 0.6 to obtain cement slurry system 5# for cementing.

[0093] Comparative Example 1

[0094] This comparative example is the same as Example 1 except that the active mineral material does not contain lepidolite ore waste residue and wollastonite powder, thereby obtaining cement 1* for cementing and cement slurry system 1* for cementing.

[0095] Comparative Example 2

[0096] This comparative example is the same as Example 1 except that the composite reinforcing material does not contain the early strength material, and obtains cement 2* for cementing and cement slurry system 2* for cementing.

[0097] Comparative Example 3

[0098] This comparative example is the same as Example 1 except that the composite reinforcing material does not contain the elastic-toughness material, and obtains cement 3* for cementing and cement slurry system 3* for cementing.

[0099] Comparative Example 4

[0100] This comparative example is the same as Example 1 except that the composite reinforcement material does not contain the micro-expansion material, and obtains cement 4* for cementing and cement slurry system 4* for cementing.

[0101] Test example

[0102] 1. Referring to GB / T19139 oil well cement test method, the engineering properties such as density, water loss, fluidity, anti-channeling coefficient, and thickening time of the cement slurry systems prepared in Comparative Examples 1 to 4 and Examples 1 to 5 were tested. The results are shown in Table 6.

[0103] Table 6

[0104]

[0105] According to the data in Table 6, the cement slurry systems prepared in Examples 1 to 5 have a water loss of less than 40 ml and a fluidity of more than 18 cm, which can meet the construction requirements well, and have a low SPN value (anti-channeling coefficient), excellent anti-channeling ability, and significantly shortened thickening time. Compared with Example 1, the engineering properties of the cement slurry systems of Comparative Examples 1 to 4 have declined to varying degrees.

[0106] 2. Referring to GB / T19139 oil well cement test method, the compressive strength and elastic modulus of the cement slurry systems prepared in Comparative Examples 1 to 4 and Examples 1 to 5 were tested. The results are shown in Table 7.

[0107] Table 7

[0108]

[0109] According to the data in Table 7, the cement slurry system prepared in the embodiment of the present invention can be quickly hydrated and develop strength rapidly under low temperature environment, which is beneficial to shorten the cementing waiting time of shallow oil and gas wells. In addition, it can be seen from the elastic modulus that the present invention effectively improves the toughness of cementing cement, and the obtained cement paste has excellent toughness, which can meet the performance requirements of cement slurry in low temperature cementing engineering and effectively solve the problem of insufficient toughness of cement paste under low temperature environment.

[0110] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A cement suitable for coalbed methane cementing, characterized in that: The following raw materials are included in weight percentage: G grade cement: 55-75wt%; Active mineral materials: 15-20wt% Composite reinforcement material: 3-5wt% Lightening agent: 5~15wt% Fluid loss reducer: 1-3wt%; Dispersant: 1~2wt%.

2. The cement suitable for coalbed methane cementing according to claim 1, characterized in that: The active mineral material is a mixture of fly ash, microsilicon, lithium mica ore waste residue and wollastonite powder in a mass ratio of 3:2:1:

1.

3. The cement suitable for coalbed methane cementing according to claim 2, characterized in that: The SiO2 content in the fly ash is 40-50wt%, and the Al2O3 content is 35-45wt%; the SiO2 content in the microsilicon is 96wt%, and the particle size of the microsilicon is 0.05-0.30μm; the SiO2 content in the lithium mica mine waste is 50-60wt%, the Al2O3 content is 25-30wt%, and the CaSO4 content is 3-5wt%; the SiO2 content in the wollastonite powder is greater than 50wt%, the CaO content is greater than 40wt%, and the average particle size of the wollastonite powder is 50μm.

4. The cement suitable for coalbed methane cementing according to claim 1, characterized in that: The composite reinforcement material is a mixture of an early strength material, an elastic toughness material and a micro-expansion material in a mass ratio of (14-16):(2-3):(2-3).

5. The cement suitable for coalbed methane cementing according to claim 4, characterized in that: The early strength material is prepared by mixing active component A, active component B and reinforcing component in a mass ratio of 1:3:1, and the preparation method is as follows: S1, mixing the active component A and the reinforcing component to obtain powder A; S2, placing active component B in a ball mill and ball milling it at a speed of 500 rpm for 6 hours to obtain powder B; S3, pneumatically mixing powder A and powder B to obtain an early strength material; Preferably, the active component A is prepared by mixing carbide slag, biomass slag and aerated concrete waste in a mass ratio of 5:4:1, and the preparation method is as follows: S11, placing carbide slag, biomass slag and aerated concrete waste in a ball mill according to a mass ratio of 5:4:1, with a liquid-to-solid ratio of 1.0, and ball milling at a speed of 400 rpm for 72 hours to obtain slurry A; S12, placing slurry A in a sealed stirring tank, adding 1 wt% of the solid mass of the slurry A in a dispersing stabilizer, stirring at a temperature of 80° C. for 72 h, to obtain slurry B; S13, placing slurry B in a centrifugal device for liquid-solid separation, and drying the solid phase at the bottom of the liquid-solid separation into dry powder to obtain active component A; More preferably, the CaO content in the carbide slag is 65-70wt%, and the pH is 12-13; the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the particle size is less than 325 mesh; the aerated concrete waste is composed of tobermorite, semi-crystalline CSH (I), CSH gel and silicon dioxide, and the powder fineness is less than 600 mesh after crushing and grinding; the dispersion stabilizer is a mixture of ketone-aldehyde condensation product and microcrystalline cellulose; Preferably, the active component B is prepared by mixing modified zirconium silicon slag, silicon manganese slag, phosphorus slag and alkaline slag in a mass ratio of 3:2:1:1, and the modified zirconium silicon slag is prepared by making slurry C from zirconium silicon slag, and the slurry C is subjected to solid-liquid separation after neutralization, water washing and impurity removal, and then high-temperature drying and grinding to obtain the product; More preferably, the modified zirconium silicon slag has a SiO2 content of ≥90wt%, a neutral pH, and a powder particle size of less than 325 mesh; the powder particle size of the silicon manganese slag is less than 325 mesh, the SiO2 content is 35-40wt%, the Al2O3 content is 9-12wt%, the CaO content is 25-28wt%, and the MgO content is 6-11wt%; the SiO2 content of the phosphorus slag is 35-40wt%, and the CaO content is 42-48wt%; the CaCO3 content of the alkali slag is 40-45wt%, the CaSO4 content is 7-10wt%, and the CaCl2 content is 10-14wt%; Preferably, the reinforcing component is a mixture of lithium silicate and aluminum sulfate in a mass ratio of 1:2; More preferably, the purity of the lithium silicate is greater than 98 wt %, and the purity of the aluminum sulfate is greater than 98 wt %.

6. The cement suitable for coalbed methane cementing according to claim 4, characterized in that: The elastic and tough material is prepared by mixing ethylene-butyl acrylate copolymer and cellulose acetate butyrate in a mass ratio of 5:2, crushing them into fine powders, and then subjecting them to low-temperature plasma modification.

7. The cement suitable for coalbed methane cementing according to claim 6, characterized in that: The butyl acrylate content in the ethylene-butyl acrylate copolymer is 33-37 wt %; the acetyl content in the cellulose acetate butyrate is 12-15 wt %, and the butyryl content is 32-35 wt %.

8. The cement suitable for coalbed methane cementing according to claim 4, characterized in that: The micro-expanding material is a mixture of hectorite and magnesite tailings in a mass ratio of 1:3; preferably, the content of lithium magnesium silicate in the hectorite is >99wt%; the content of MgO in the magnesite tailings is 38-42wt%, and the content of SiO2 is 15-18wt%.

9. The cement suitable for coalbed methane cementing according to claim 1, characterized in that: The lightening agent is hollow glass microspheres with a density of 0.44-0.48 g / cm 3 , Dv50 is 40μm, and the compressive strength is >4000psi; the fluid loss reducer is 2-acrylamide-2-methylpropanesulfonic acid / acrylamide copolymer; and the dispersant is sulfonated acetone formaldehyde condensate.

10. A method for preparing cement for coalbed methane cementing according to any one of claims 1 to 9, characterized in that: The preparation method is as follows: G-grade cement, active mineral materials, composite reinforcing materials, lightening agents, fluid loss reducers and dispersants are uniformly mixed in various proportions to form dry powder, thereby obtaining cement suitable for coalbed methane cementing.

Citation Information

Patent Citations

  • Low-temperature early strength agent for coal bed gas well cementing and cement slurry for well cementing containing low-temperature early strength agent

    CN104194752A

  • Low-temperature early-strength low-density cement paste system for coal-bed-gas well cementation

    CN110054440A

  • Well cementing cement paste suitable for coal bed methane and preparation method thereof

    CN112456873A

  • Elastic-tough well cementation cement paste suitable for coalbed methane and preparation method thereof

    CN112500042A

  • Waste glass-carbide slag-based C-S-H gel nanocrystal nucleus early strength agent as well as preparation method and application thereof

    CN115231846A

Cited By

  • Deep coal bed gas well cementation cement paste and preparation method thereof

    CN120757336A

  • Deep coal bed gas well cementing slurry and preparation method thereof

    CN120757336B